PENERAPAN E-GOVERNMENT DALAM MENDUKUNG TRANSPARANSI DAN AKUNTABILITAS PEMERINTAH DAERAH KABUPATEN POLEWALI MANDAR - Rahmaniar Rachman; Riana Anggraeny Ridwan (Universitas Bina Taruna Gorontalo, 2023)
The aim of this research is to describe the implementation of e-Government in Polewali Mandar Regency in supporting transparency and accountability of the regional government of Polewali Mandar Regency. In this research the author looks at the application of e-Government by approaching the elements of successful e-Government implementation. Polewali Mandar Regency is one of the regencies in West Sulawesi Province which is currently continuing to develop in terms of public services. So the use of information technology is something that is mandatory for Polewali Mandar Regency at this time. This research uses descriptive type qualitative research methods. Data collection uses observation, in-depth interviews, and documentation studies. The results of this research indicate that the implementation of e-Government in Polewali Mandar Regency is still not optimal in terms of Support, Capacity and Benefits (Value).